AB0849 Spinal Brucellosis: A Study of 40 Cases in A Tunisian Hospital. (15th July 2016) - Ajlani, H.; Rekik, S.; Boussaid, S.; Sahli, H.; Cheour, E.; Elleuch, M.
Abstract : Background: Brucellosis is a major health problem in Mediterranean countries, including Tunisia. The clinical presentation of this zoonosis varies considerably, but osteoarticular involvement and spinal brucellosis particularly, is the commonest complication. Methods: This study was carried out between 2006 and 2013. Forty patients with infectious spondylodiscitis hospitalized in the department of Rheumatology were analyzed. All patients were thoroughly interrogated, subjected to a rigorous clinical examination and a battery of investigations including: complete blood count, urine analysis, blood culture, erythrocyte sedimentation rate, C-reactive protein (CRP) and serology for brucellosis. The imaging ordered including: plain X-ray of the lumbosacral spine, bone scan and magnetic resonance imaging (MRI) with contrast enhancement of the spine. Results: Ten of the forty patients (25%) proved to have spinal brucellosis. The mean age of this patients was 51 years (range 15 – 68 years) and female/male ratio: 1, 5. The mean delay of diagnosis was 7 months. The following symptoms were observed: fever in 9 patients and back pain in all patients. Other symptoms were less frequently observed, such as splenomegaly (one patient), peripheral adenopathy (two patients) and diarrhoea (one patient). Laboratory exams showed elevated erythrocyte sedimentation rate in most of them (8 patients), high levels of CRP in all patients and leukocytosis in 7 cases. Wright serology was positive in all of them. Brucella melitensis was isolated in blood cultures in 2 cases. Standard X-rays were performed in all patients; they showed signs of spondylodiscitis in the lumbar spine in 5 cases, cervical in one case and dorsal in two cases. CT-scan and MRI confirms the diagnosis and showed associated epiduritis (3cases) or abscess (4 cases). Bone biopsy and histopathological examination were performed in three cases. A combination of cycline and rifampicin was given to all patients. The duration of therapy was between 6 and 8 weeks. Conclusions: Brucellosis is present with various clinical signs in endemic areas and may simulate many diseases. The need for prompt diagnosis and treatment of spinal brucellosis is of the utmost importance to prevent serious bone destruction and severe neurologic sequelae. Disclosure of Interest: None declared